Student author as actor network? Using ANT to explore digital literacies in higher education - Gourlay, Lesley (Proceedings of the International Conference on Networked Learning, 2012)
The concept of 'digital literacies' is indeterminate and contested, arising from contrasting theoretical positions and traditions of practice and enquiry. 'Literacies' - particularly the plural - is a term which has come to be associated with New Literacies Studies (e.g. Barton 1994) and the resultant critique of the notion of generic, transferable 'skills' (e.g. Lea & Street 1998, Wingate 2006). The literacies perspective sees writing as situated social practice, and seeks to blur the categories of 'content' and writing process, arguing that they are inextricably linked. Writer subjectivity is also foregrounded and dominant forms of representation are critiqued as implicated in the reproduction of social privilege. Focusing on academic writing in particular, this paper will argue that this critique has only been partially successful in terms of influence across the sector, and that 'digital literacies' has in many contexts simply become the new term for 'IT skills'. The persistence of the 'skills' lens - with its implicit techno-rationalist focus on decontextualised procedure - can be seen in hybrid formulations such as 'digital literacy skills'. The picture is further complicated by the widespread use in popular culture of 'literacy' to denote a form of 'know-how', such as 'computer literacy'. I will argue that the fundamental shift in understanding demanded by the original (once-disruptive) 'literacies' critique has been largely lost through a process of domestication of the term. In response, actor-network theory (ANT) (Latour 2005) is proposed as a complimentary orientation which may allow new understandings of relationships between texts, contexts and practices, recasting the author and reader as enmeshed in complex posthuman (e.g. Hayles 1999) networks of human and non-human actors. This standpoint may serve to creatively undermine seemingly stable categories such as 'text', 'author' and 'machine' in generative ways when seeking to explore networked, digitally-mediated forms of writing and representation. This will be illustrated with reference to a JISC-funded study (JISC 2011) in which multimodal journaling will be deployed to explore these networks in day-to-day student practice in a specialist postgraduate institution. It will conclude with suggested implications for researchers and practitioners concerned with writing and representation in higher education.